PENGARUH LINGKUNGAN KERJA, BUDAYA ORGANISASI DAN ETIKA KERJA TERHADAP KINERJA KARYAWAN: STUDI KAUSAL PADA KARYAWAN PONDOK PESANTREN LA TANSA DI KABUPATEN LEBAK - Ade Jaya Sutisna; Fardan Dzaki Firdaus (Universitas La Tansa Mashiro, 2024)
The purpose of this research is to analyze the influence of work environment, organizational culture and work ethics on employee performance of La Tansa Islamic Boarding School in Lebak Regency, and thus, improve employee performance level. A questionnaire-based survey was conducted at La Tansa Islamic Boarding School in Lebak Regency, analyzing a sample size of 65 employees. The results of path analysis modeling revealed that work environment has a positive and significant effect on work ethics, organizational culture has a positive and significant effect on work ethics, work environment has a positive and significant effect on employee performance, organizational culture has a positive and significant effect on employee performance, work ethics has a positive and significant effect on employee performance, work environment has a positive and significant effect on employee performance through work ethics and organizational culture has a positive and significant effect on employee performance through work ethics. This study provides important contributions in the field of work environment that can be useful for La Tansa Islamic Boarding School in Lebak Regency to recognize the importance of work environment to improve employee performance. The findings also provide significant implications for organizations to better understand the importance of work environment, which will help to improve organizational success.